RHYTHMS OF HERITAGE: PRESERVING AND RECONTEXTUALIZING FOLK MUSIC THROUGH MODERN JAZZ IMPROVISATION - Porwal, Tina; Deshpande, Leena; Srivastava, Swati; B, Damodaran; Khetani, Vinit; Palkhe , Vilas (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Folk music is a cultural reminiscence, social ideals, and historical records of people, but numerous traditions are struggling with the issue of continuity in the environment of globalization and shifting musical realities. This article discusses how modern jazz improvisation has been used as a creative and culturally sensitive tool to maintain and recontextualize folk music traditions. Instead of seeing preservation as a conservation that is unchanging, the study conceptualizes heritage as a living process that continues to survive by changing. Using ethnomusicological viewpoints, jazz improvisation theory, and intercultural theory the study examines how rhythmic patterns, modal systems and performance practices of folk music can be incorporated in the modern jazz environment without the erosion of cultural identity. The paper shows that improvisation makes it possible to have a dynamic dialogue between tradition and modernity and the folk elements can keep the symbolic and emotional meaning they have and broaden their expressive opportunities that are achieved through harmonic reinterpretation, rhythmic adaptation, and group performance. The problematization of jazz improvisation as a cultural negotiation and sustainability points to the research as a means of heritage preservation through a living archive and pedagogical tool, as well as an ethical platform. The results provide a wider-ranging discourse on the field of musicology and performance studies by establishing preservation through transformation as a possible paradigm of maintaining traditional music in the context of the contemporary artistic practice.